Effects of anomalous climatic events on the structure of fish larvae assemblages in the eastern Amazon - Cajado, Ruineris Almada; Oliveira, Lucas Silva de; Silva, Fabíola Katrine Souza da; Zacardi, Diego Maia; Andrade, Marcelo Costa (Frontiers in Environmental Science, 2022)
The reproduction of neotropical fish is linked to environmental stimuli that act as triggers in this process. Thus, it is possible to affirm that specific environmental changes can delimit most fish’s period and reproductive success. El Niño Southern Oscillation phenomena (ENSO) influence rainfall and, consequently, hydrological dynamics, affecting several fish population aspects, especially reproductive aspects. However, in the Amazon, empirical evidence of the effect of anomalous climatic events on fish reproduction is incipient. In this sense, we investigated the taxonomic and functional structure of parental fish larvae stocks and how species modulate their reproductive activities before (2013 and 2014) and during La Niña (2018) and El Niño (2019) events. The data evidence that the larval assemblages suffered alterations in the taxonomic and functional composition between the three analyzed periods and a pattern of temporal distribution with a high influence of environmental variables. Flow, pH, and electrical conductivity were the most important variables to modulate fish reproductive intensity between periods. The species seem to respond to combinations of these variables that reflect environmental conditions conducive to biological recruitment according to their ecological characteristics, allowing the perpetuation or decline of their abundance in each period. All species of commercial interest associated with the neutral period showed a sharp decline in the subsequent moments. These results suggest that the incidence of anomalous climatic events added to regional fisheries exploitation can negatively affect the phenology and demographic patterns of larvae assemblages on a short temporal scale. During the neutral period, the community was dominated by larvae of periodic large, herbivores, piscivores, epibenthic maneuverable, and nektonic burst swimmers. The decrease in the abundance of certain functional groups at the neutral and La Niña period favored an accelerated ecological succession during the El Niño period, due to the increase of species from basal trophic levels (planktivores), generalists (omnivores), highly resilient (intermediate strategists), sedentary, short-distance migrants and little commercially exploited. Thus, the results contribute to the understanding of the interactions between anomalous climatic events and the reproduction of fish with different ecological characteristics in the Amazon River.